Minimum wages in an automating economy - Marcel Steffen Eckardt (Journal of Public Economic Theory, 2021)
We explore the suitability of the minimum wage as a policy instrument for reducing emerging income inequality created by new technologies. For this, we implement a binding minimum wage in a task-based framework, in which tasks are conducted by machines, low-skill, and high-skill workers. In this framework, an increasing minimum wage reduces the inequality between the low-skill wage and the other factor prices, whereas the share of income of low-skill workers in the national income is nonincreasing. Then, we analyze the impact of an automating economy along the extensive and intensive margins. In a setting with a minimum wage, it can be shown that automation at the extensive margin and the creation of new, labor-intensive tasks do not increase the aggregate output in general, as the displacement of low-skill workers counteracts the positive effects of cost-savings. Finally, we highlight a potential trade-off between less inequality of the factor prices and greater inequality of the income distribution when a minimum wage is introduced into an automating economy.
Keywords: 330; automation; displacement effects; employment; inequality; labor demand; minimum wage; tasks; wages